Key Benefits of Enterprise Surveys for Improving the Business Enabling Environment (BEE) - Liepina, Sanda; Nicholas, Dina; Novoseletsky, Edgard (World Bank, Washington, DC, 2012)
The private enterprise partnership (PEP) for Eastern Europe & Central Asia has been surveying the small and medium enterprise (SME) sector for 10 years. What began in 1996 as a survey of business practices among 250 entrepreneurs in Ukraine has grown into annual or biannual surveys of administrative barriers to business development in five countries. The SME surveys have proven vital for PEP in building its regional business enabling environment program. Specifically, running regular SME surveys introduces four key benefits for business enabling environment work: 1) building visibility for International Finance Corporation (IFC); 2) building capacity for a new local team; 3) motivating governments to reform; and 4) monitoring project results and assessing the impact of change to BEE.